Effect of microstructure and crystallographic texture on mechanical anisotropy of Ti-Nb microalloyed hot rolled 800 MPa HSLA steel - Das Bakshi S.; Javed N.; Sasidhar K.N.; Dhande T.; Sharma V.; Mukherjee M. (My University, 2025)
The impact toughness of a Ti+Nb HSLA steel plate, conventionally hot rolled in the austenitic region, were measured at four different directions at 0 °C, −20 °C and −40 °C respectively. The microstructure was characterised using light optical microscope, scanning electron microscope (SEM) followed by evaluation of hot rolled texture using X-ray diffraction (XRD) and orientation distribution function (ODF) obtained from electron back-scattered diffraction (EBSD). The anisotropy in the yield strength (YS) and Charpy impact toughness (CVN) were examined in the light of orientation distribution function (ODF) obtained from EBSD. The skeleton lines, showing intensity distribution, f(g), of the fcc-to-bcc transformation texture, namely the α-fiber (⟨110⟩∥ RD), the γ-fiber (⟨111⟩∥ ND) and ε-fiber (⟨110⟩∥ TD) are considered to explain the observed anisotropy along with microstructural features. The major components like, {112}⟨110⟩ {113}⟨110⟩ {332}⟨113⟩ {111}⟨112⟩ and {111}⟨110⟩ their relative intensity distribution, are found to cause the observed anisotropy in yield strength and impact toughness. A stronger presence of {113}⟨110⟩ component of the α-fiber over relatively weaker {332}⟨113⟩ component of the ε-fiber further augments the observed toughness anisotropy. In absence of any microstructural banding, strong the presence of {113}⟨110⟩ and {112}⟨110⟩ can also cause delamination in ductile fracture mode. © 2017 Elsevier Inc.